DETERMINANTS OF CROWDFUNDING ACCEPTANCE FOR MAINTENANCE OF SCHOOL FACILITIES - Muhammad Ridzwan Yap Abdullah , Mohammed Hariri Bakri (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
Public schools have become one of the significant educational institutions for all Malaysians. It has been used to teach Malaysians to be part of a community, having diversified cultures, races, and religions. As such, students have learned to be more compassionate, considerate, and kind to others. However, most public schools in Malaysia have been operating for many years, which has resulted in neglect and damage due to aging and improper care and maintenance. The lack of regular maintenance and care is mainly attributed to insufficient budget allocations from the federal government. This research focused on determining the factors that could influence the prospective investors’ intention to donate in this crowd-funding project. The research selected the UTAUT model to determine the prospective investor’s intention toward donating money to the crowd-funding project. To test the developed hypotheses in this study, descriptive research was adopted by applying a self-administered questionnaire distributed to respondents. For this study, convenience sampling was selected, whereby 384 respondents responded and answered the questions. All the independent variables have shown that they were positively significant to the intention of the prospective investor. Hence, the intention of prospective investors is influenced by performance expectancy, effort expectancy, social influence, facilitating conditions, and trustworthiness. This research successfully contributed to the knowledge in this field by applying the UTAUT factor in the context of crowd-funding for the maintenance of public schools in Malaysia. The research could act as a guideline or reference to enhance the public’s intention to donate in a crowd-funding project and it is hoped that this research could be used as a standard and reference for future crowd-funding initiatives by the government